ANALISIS LINGKUNGAN BUDAYA, POLITIK, DAN HUKUM GLOBAL TERHADAP PEMASARAN GLOBAL - Suhairi Suhairi; Putri Apriyani Rangkuti; Suci Afria Sasty Siregar; Padrie Payung Siregar (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
This research examines the analysis of the global cultural, political and legal environment on global marketing. This research uses descriptive qualitative research. The results of this research show that analysis of the global cultural, political and legal environment is very important in designing global marketing strategies. This environment has a direct impact on how companies market their products or services in the global market. Global marketing has a positive influence on the Indonesian economy in several aspects, including; open export markets, easy access to foreign capital, tight competition with products from other countries and others.